2003
DOI: 10.1590/s0102-311x2003000400002
|View full text |Cite
|
Sign up to set email alerts
|

Sexualidade e medicina: a revolução do século XX

Abstract: This paper discusses the role of medicine, ranging from the normative and technological control of women's sexuality ad reproductive process (childbirth, breastfeeding, contraception, and treatment of infertility) through the construction of a new (biological and social) reproductive model, based on a radical change of identities, relations, and forms of union between the sexes (a break with the traditional concept of marriage, growth of open unions, serial monogamy, etc.). This model is sustained by a radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
18

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
0
2
0
18
Order By: Relevance
“…Loyola [27] alertou, no início dos anos 2000, que "a liberação do sexo" teria como efeito deixar todo mundo em busca de seu "gênero", de sua identidade genérica e sexual, com cada vez menos respostas possíveis, considerando-se a circulação dos signos e a multiplicidade dos prazeres. Tratava-se, em suma, da transformação das questões de identidade sexuada nas de um comércio de signos, de um jogo irônico da indiferença sexual.…”
Section: N T R O D U ç ã Ounclassified
See 1 more Smart Citation
“…Loyola [27] alertou, no início dos anos 2000, que "a liberação do sexo" teria como efeito deixar todo mundo em busca de seu "gênero", de sua identidade genérica e sexual, com cada vez menos respostas possíveis, considerando-se a circulação dos signos e a multiplicidade dos prazeres. Tratava-se, em suma, da transformação das questões de identidade sexuada nas de um comércio de signos, de um jogo irônico da indiferença sexual.…”
Section: N T R O D U ç ã Ounclassified
“…Tratava-se, em suma, da transformação das questões de identidade sexuada nas de um comércio de signos, de um jogo irônico da indiferença sexual. Esses desafios a sexualidade teria de enfrentar no século XXI" [27].…”
Section: N T R O D U ç ã Ounclassified
“…These issues are still seen as taboos, which are difficult to discuss. [26][27][28][29][30][31] Studies have shown that in the history of Brazilian society, concepts and practices related to sex and sexuality are rooted in a traditionally patriarchal, sexist culture linked to Christian religious dogma. Therefore, women feel that they are stuck in a restrictive and punishing society, while men live in a world without clearly-defined rules or reflections, in terms of the ethics of those involved.…”
Section: Sex and Sexualitymentioning
confidence: 99%
“…Parte do atual controle da sexualidade pela medicina é feita pelos sexólogos 6 . Nos trabalhos pioneiros de Béjin 7,8 , o poder científico dos sexólogos contemporâneos é explicado pela obtenção de um consenso perante uma definição empírica relativamente precisa de "saúde sexual".…”
Section: Introductionunclassified